Self-assembled NIR nanovesicles for long-term photoacoustic imaging in vivo. Issue 70 (27th July 2015) - An, Hong-Wei; Qiao, Sheng-Lin; Hou, Chun-Yuan; Lin, Yao-Xin; Li, Li-Li; Xie, Han-Yi; Wang, Yi; Wang, Lei; Wang, Hao
Abstract : We report a supramolecular approach for preparation of photostable NIR nanovesicles based on a cyanine dye derivative as a photoacoustic (PA) contrast agent for high-performance nano-imaging. Abstract : We report a supramolecular approach for the preparation of photostable NIR nanovesicles based on a cyanine dye derivative as a photoacoustic (PA) contrast agent for high-performance nano-imaging.